Monetary and Social Incentives in Multi-Tasking: The Ranking Substitution Effect - Matthias Stefan; Jürgen Huber; Michael Kirchler; Matthias Sutter; Markus Walzl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Rankings are intended as incentive tools on labor markets. Yet, when agents perform multiple tasks - not all of which can be ranked with respect to performance -, rankings might have unintended side-effects. Based on a dynamic model of multi-tasking, we present an experiment with financial professionals in which we identify hidden ranking costs when performance in one task is ranked while in another prosocial task it is not. We find that subjects lagging behind (leading) in the ranked task devote less (more) effort to the prosocial task. We discuss implications for optimal incentive schemes in organizations with multitasking.
Keywords: C93; D02; D91; 330; multi-tasking decision problem; rank incentives; framed field experiment; finance professionals